Investigating AGN/Starburst activities through ALMA multi-line observations in the mid-stage IR-bright merger VV 114. Issue Volume 10:Issue S309(2014) (9th February 2015) - Saito, Toshiki; Iono, Daisuke; Yun, Min S.; Ueda, Junko; Espada, Daniel; Hagiwara, Yoshiaki; Imanishi, Masatoshi; Motohara, Kentaro; Nakanishi, Kouichiro; Sugai, Hajime; Tateuchi, Ken; Lee, Minju; et al.
Abstract: We present ALMA cycle 0 observations of the luminous merger VV 114. One of the main goals is to investigate mechanisms of molecular line ratio enhancement. Regions with the high 12 CO (1–0)/ 13 CO (1–0) and 12 CO (3–2)/ 12 CO (1–0) is located at a central filamentary structure (∼6 kpc) in VV 114. The filament consists of the eastern nucleus and the overlap region, where the galaxy disks are colliding. We also investigate these molecular line ratios on the Kennicutt-Schmidt law. VV 114 fills a gap between the "starburst" sequence and the "normal disk" sequence, and regions with the high ratios show the high ΣSFR and ΣH2 . We suggest that the high ratios in VV 114 are due to star-forming activities in the both progenitor's nuclei and the merger-induced overlap region.